TEACHING READING COMPREHENSION USING NEUROLOGICAL IMPRESS METHOD AT JUNIOR HIGH SCHOOL - Lina Ayudiyah; Dian Erlina; Fitri Alya Okta Sukma (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2025)
Reading is a fundamental skill in education, and its importance cannot be overstated. It plays a crucial role in language learning and academic success. The goals of this study were to determine whether there was a significant improvement and whether there was a substantial difference in students’ reading comprehension achievement before and after the implementation of the Neurological Impress Method. The Neurological Impress Method for eighth-grade students at SMPN 7 Palembang. This study was conducted over 12 meetings, employing a quasi-experimental methodology. 68 students were selected as a sample using the convenience sampling technique. There were two groups: control (VIII.9) and experimental (VIII.10). Pre-test and post-test were administered to both groups during data collection. The researcher analyzed the data using SPSS version 26. Based on the outcome of the Paired Sample T-Test, the p-value was 0.000, which was less than 0.05, and the t-value was 8.308, which was higher than the t-table df=33 (2.035). Therefore, it is possible to conclude that students' pre-test and post-test scores improved significantly in the experimental group taught using the Neurological Impress Method. Following the results of the Independent Sample T-Test, the p-value was 0.004, which was less than 0.05, and the t-value was 2.984, which was higher than the t-table df=66 (1.997). As a result, students' pre-test scores differed significantly between the control and experimental groups. The findings of this study demonstrated that the Neurological Impress Method improved students' reading comprehension and could be used as an alternate method for teaching reading comprehension